2022
DOI: 10.1088/1741-2552/ac7893
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop transcranial ultrasound stimulation with a fuzzy controller for modulation of motor response and neural activity of mice

Abstract: Objective. We propose a closed-loop transcranial ultrasound stimulation (TUS) with a fuzzy controller to realize real-time and precise control of the motor response and neural activity of mice. Approach. The mean absolute value (MAV) of the electromyogram (EMG) and peak value (PV) of the local field potential (LFP) were measured under different ultrasound intensities. A model comprising the characteristics of the MAV of the EMG, PV of the LFP, and ultrasound intensity was built using a neural network, and a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Recently, Yu et al (2021) showed that ultrasound can elicit direct responses in the rodent brain, independent of hearing. In our last research, we performed closed-loop ultrasound stimulation experiments, and found that the amplitude changes and dynamic responses on the electromyogram and LFP in normal mice were substantially similar to those in deaf mice, demonstrating that ultrasound induces motor responses and neural responses by stimulating brain tissue rather than indirect auditory effects ( Yuan et al, 2022 ). Therefore, we speculate that the changes in theta and gamma rhythms induced by ultrasound under peak and trough stimulation are not the results of auditory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yu et al (2021) showed that ultrasound can elicit direct responses in the rodent brain, independent of hearing. In our last research, we performed closed-loop ultrasound stimulation experiments, and found that the amplitude changes and dynamic responses on the electromyogram and LFP in normal mice were substantially similar to those in deaf mice, demonstrating that ultrasound induces motor responses and neural responses by stimulating brain tissue rather than indirect auditory effects ( Yuan et al, 2022 ). Therefore, we speculate that the changes in theta and gamma rhythms induced by ultrasound under peak and trough stimulation are not the results of auditory effects.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study [51], different types of controllers were used to automatically adjust the ultrasound intensities of distinct ultrasound stimulations based on the feedback of real-time parameters (the mean absolute value of the EMG and peak value of the LFP). We demonstrated that a closed-loop TUS with a fuzzy controller can achieve tracking control of the motor response and neural activity of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a closed-loop brain neuromodulation system combining existing physical neuromodulation technologies, such as optogenetics, deep brain stimulation [ 176 ], transcranial electrical stimulation [ 177 ], and transcranial magnetic stimulation has been developed [ 178 ]. There have also been recent reports on closed-loop ultrasound neuromodulation systems, owing to the advantages of closed-loop brain stimulation [ 179 181 ] (Fig. 6 ).…”
Section: Ultrasound Bci-preliminary Studies Based On Eegmentioning
confidence: 99%
“…Based on the CLTUS system, Yuan et al. [ 181 ] added a fuzzy algorithm to the control program to achieve timely and accurate control of the limb movement and nervous system of mice. The target of the ultrasound stimulation in this study was the motor cortex.…”
Section: Ultrasound Bci-preliminary Studies Based On Eegmentioning
confidence: 99%